2012
DOI: 10.1093/mnras/sts217
|View full text |Cite
|
Sign up to set email alerts
|

Intranight optical variability of  -ray-loud narrow-line Seyfert 1 galaxies

Abstract: The Large Area Telescope (LAT) onboard the Fermi Gamma Ray Space Telescope has detected γ-ray emission in about half-a-dozen Narrow Line Seyfert 1 (NLSy1) galaxies. This indicates the presence of relativistic jets in these sources similar to blazars and radio galaxies. In an attempt to have an idea of the intranight optical variability (INOV) characteristics of these γ-ray loud NLSy1 galaxies, we have carried out optical flux monitoring observations of three NLSy1 galaxies detected by Fermi/LAT: 1H 0323+342, P… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
41
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 55 publications
(46 citation statements)
references
References 46 publications
4
41
1
Order By: Relevance
“…Previous studies, conducted to RL-NLSy1s, had already supported the idea that, when compared with blazars, RL-NLSy1s are particularly similar to FSRQs (e.g. Paliya et al 2013;Foschini et al 2015;Paliya & Stalin 2016). Provided that RL-NLsy1s are hosted by spiral galaxies, what our findings suggest, might be a substantive contribution since blazars are known to be hosted by elliptical galaxies and powered by massive black holes.…”
Section: Agn-host Connectionsupporting
confidence: 80%
“…Previous studies, conducted to RL-NLSy1s, had already supported the idea that, when compared with blazars, RL-NLSy1s are particularly similar to FSRQs (e.g. Paliya et al 2013;Foschini et al 2015;Paliya & Stalin 2016). Provided that RL-NLsy1s are hosted by spiral galaxies, what our findings suggest, might be a substantive contribution since blazars are known to be hosted by elliptical galaxies and powered by massive black holes.…”
Section: Agn-host Connectionsupporting
confidence: 80%
“…This demonstrates, for the first time, the reality of very low-amplitude (∆MR ≤ 0.05) microvariability events for 1H 0323+342. Previously, Paliya et al [4] and Paliya et al [5] reported detecting the presence of intranight optical variability (INOV) for 1H 0323+342. These results report the presence of low-level linear trends occurring during a single night, but not microvariations.…”
Section: Resultsmentioning
confidence: 99%
“…The F -test does not require additional efforts in comparison, for example, to the C-test, and thus Paper I has contributed to popularize its use (e.g. Joshi et al 2011;Joshi & Chand 2013;Paliya et al 2013;Goyal et al 2013). Nevertheless, interest for developing new test procedures has not decayed, and a number of test adjustments have been considered.…”
Section: Introductionmentioning
confidence: 99%